Best Answer

Okay so to solve this expression you use Pemdas or Gemdas it doesn't matter they're both the same thing. The first step in Pemdas is Parenthesis so you do 6×2 which is 12 then you do 6×1 which is 6 and since there is a addition sign you add 12+6 which gets you a sum of 18

So your answer will be 18

Study guides

☆☆

Q: How to solve this 6(2 + 1)?

Write your answer...

Submit

Still have questions?

Related questions

[ 62 - 63 = 1 ] is not an equation, and there's nothing to solve. It's a simple, incorrect statement.

In reverse: 63 - 1 = 2n = 62 62 / 2 = 31 Now as the question: (2 x 31) + 1 = 62 + 1 = 63 Q.E.D.

62 is composite because it can be multiplied by one and other numbers. 1*62=62, 2*31, 62*1=62 if it was prime, then it would just be 1*62=62.

62t = 82 divide both sides by 62 = 82/62 = 41/31 check ( use 82/62 ) 62(82/62) = 82 as you see 62 cancels with 62 82 = 82 checks

62 + 1 = 63

100% of 62 = 100% * 62 = 1 * 62 = 62

1, 2, 31, 62

The four factors of 62 are 1, 2, 31, and 62. The factor pairs of 62 are (1, 62) and (2, 31)

62 can be written as 62/1.

62 x 1/6 = 62 x 0.16667 = 10.33354

62

When the term # = t, and the term = m, the equasion is 2(x2) = n.Therefore, to solve this equation, solve: 2(62).62 = 362(36) = 72

People also asked